Penggunaan Kolokial pada Channel YouTube “Kok Bisa?” - Bhudeci, Dhio Rezky; Ayuningrum, Gita; Jubaedah, Siti; Lapasau, Merry; Hidayat, Ryan (Jurnal Ragam Pengabdian, 2026)
This study aims to identify and analyze the use of colloquial language on the YouTube channel *Kok Bisa?* from a sociolinguistic perspective. The data were taken from videos in the playlist *Taman Edukasi: Learning Science So Fun!*. This research employed a descriptive methodological approach and a theoretical framework based on Charles A. Ferguson’s Diglossia theory and Howard Giles’ Communication Accommodation Theory (CAT). Data were collected using the Free Listening Engagement (SBLC) and note-taking techniques, then analyzed through the interactive model of Miles, Huberman, and Saldana, consisting of data collection, reduction, and conclusion drawing. The findings reveal that the educational videos apply diglossia and communication accommodation strategies to improve comprehension and establish familiarity with viewers. The identified colloquial forms include single words, clipped words, vowel changes, and affixation. The use of colloquial language effectively simplifies complex scientific concepts, making them more accessible and engaging for students. This effectiveness is supported by positive responses from viewers in the YouTube comment section. The study contributes practical insights for educators and content creators in designing educational videos that communicate learning materials more effectively through appropriate sociolinguistic strategies.